Adaptive reuse of heritage timber building in consideration of technical aspects. Case study of Mulong old mosque and Kelantan Islamic Museum, Kota Bharu, Kelantan / Juliza Mohamad - Mohamad, Juliza (2011)
This research is about a study on adaptive reuse of heritage timber building in consideration of technical aspects. In Malaysia, it is estimated that there are only a few numbers of heritage timber building such palace, mosque and Malay traditional house left – a dramatic loss. Some of the heritage timber buildings were damaged because of lack of maintenance and few were abandoned, and there were also few buildings were burnt down. A few numbers of heritage timber buildings were converted their function into a new function. For example, a royal palace was converted into a museum, i.e. Istana Jahar in Kelantan. The characteristics of heritage buildings which were built to response with the climatic conditions need to be adjust to adapt new modern technology in consider to fulfill the requirement for a new function. There is also lack of awareness on conserving the heritage timber building. No specific guidelines provided for conserving a heritage timber building. The aim of this research is to undertake a study exploring the heritage timber buildings which currently have been converted into another building function to find solution on how to adapt the new requirement, i.e. new modern technology such as electricity, air-conditioning system and water plumbing system to make the building well functioned. The research also to study the common problems on heritage timber buildings and its solution or building tiber building treatment. A proper methodology was adopted in this dissertation to fulfill the objectives. The methodology includes reviewing related books, journals, working papers, and articles from internet. Case studies were also applied in this dissertation and were analyzed through physical observation. Two heritage buildings were chosen; the Mulong Old Mosque and Kelantan Islamic Museum, Kota Bharu, Kelantan. Apart from that, this research could also act as a catalyst for future research on the standards and practice of museum and also on the adaptive re-use activities in Malaysia.